Friends of the Earth : sale of the centrury? : the World Trade Organisation's fourth ministerial. - Friends of the Earth International (FoEI) (Amsterdam : FoEI, 2001)
Verzamelmap bestaat uit:- The world trade system : how it works and what's wrong with it- The world trade system : winners and losers - a resource book- Toward sustainable economies : challenging neoliberal economic globalisation- Sale of the Century? : the WTO's 4th ministerial - briefing No. 3 : services : the implications of current trade negotiations- Sale of the Century? : the WTO's 4th ministerial - briefing No. 4 : peoples' food sovereignty : part 1 - the implications of current trade negotiations- Sale of the Century? : the WTO's 4th ministerial - briefing No. 5 : peoples' food sovereignty : part 2 - a new multilateral framework for food and agriculture
Engels
Brochure
Keywords: wereldhandel; duurzaamheid; voedseldistributie